2021
DOI: 10.1016/j.eats.2021.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Needle Arthroscopic All-Inside Repair of Meniscal Tears Under Local Anesthesia

Abstract: Needle arthroscopy has experienced a substantial increase in image quality due to technical innovation, which has brought needle arthroscopic interventional possibilities along. Repair of meniscal tears is gaining popularity relative to meniscectomy and may be such a procedure that is suitable for needle arthroscopy. We here present a needle arthroscopic technique for all-inside repair of meniscal tears in the red zone and redewhite zone. With the use of local anesthesia only, the procedure is easy to perform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Arthroscopic, endoscopic, and, recently, nanoscopic procedures have emerged in this context. 10 , 11 , 12 , 13 , 14 , 16 , 17 …”
Section: Discussionmentioning
confidence: 99%
“…Arthroscopic, endoscopic, and, recently, nanoscopic procedures have emerged in this context. 10 , 11 , 12 , 13 , 14 , 16 , 17 …”
Section: Discussionmentioning
confidence: 99%
“…In line with previous research on bedside needle arthroscopy, we observed that it is an easy technique to perform for the physician, and welltolerated by the patient. 3,[5][6][7][8][9][10] When considering this technique, it is important to appreciate the limitations of this presentation and of the technique itself. First, all photos and videos presented here were fabricated for educational purposes on cadaveric specimens.…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous research on bedside needle arthroscopy, we observed that it is an easy technique to perform for the physician, and well-tolerated by the patient. 3 , 5 , 6 , 7 , 8 , 9 , 10 …”
Section: Discussionmentioning
confidence: 99%
“…Others have demonstrated its use for more complicated procedures, such as meniscal repair or as an adjunct to anterior cruciate ligament repair. 13,14 Having consistently good visualization of the tibial footprint can potentially decrease technical difficulty and lessen surgical time.…”
Section: Discussionmentioning
confidence: 99%